Predictors of In-hospital Outcomes of Community-acquired versus Hospital-acquired Acute Kidney Injury in Patients Admitted to a Tertiary Care Hospital: A Prospective Study - Gaurav Shekhar Sharma; Ranjeeta Kumari; Sharon Kandari; Gaurav Jain; Farhanul Huda; Anupama Bahadur; Ravi Kant (Journal of Medical Evidence)
Background: Sparse data is available comparing the outcome of Community-acquired acute kidney Injury (CA-AKI) and Hospital-acquired acute kidney injury (HA-AKI). Aims: This study was undertaken to compare the demographic, clinical spectrum and in-hospital outcomes of CA-AKI versus HA-AKI. Patients and Methods: A prospective cohort study was conducted from October 2020 to December 2021 in the inpatient departments (IPDs) of a tertiary-care referral centre in north India. A total of 65 patients with CA-AKI and 32 patients with HA-AKI were enrolled. The characteristics and outcomes of AKI in both groups were compared. Results: The mean age of patients in the CA-AKI and HA-AKI groups was 46.7 years and 45.5 years respectively. The CA-AKI group had significantly higher baseline serum creatinine, serum creatinine at admission, proportion of patients requiring renal replacement therapy, proportion of patients having oligo-anuria and hyperkalemia at presentation. Despite more patients in the CA-AKI group being in AKI-Stage 3 at presentation, in-hospital mortality was observed to be lower in this group. However, on comparing the overall survival, both groups were found to be comparable. The independent predictors of mortality were the presence of lung disease and the requirement of vasopressor support at presentation. Conclusion: It was observed that both recovery and dialysis dependency were more common in patients with CA-AKI. Both groups had comparable overall survival. Only two factors, i.e. the presence of lung disease and the requirement of vasopressor support at presentation predicted the survival of AKI patients. The type of AKI was not an independent predictor of mortality in such patients.